Pengaruh Budaya Kerja dan Organizational Citizenship Behavior Terhadap Kinerja Karyawan PT. Kaltrabu Indah Tour dan Travel Banjarmasin - Sanjaya, Fanlia Adiprimadana (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2020)
This research aims to study, analyze, and determine the effect of Work Cultur and, Organizational Citizenship Behavior on Employee Performance PT Kaltrabu Indah Tour & Travel Banjarmasin. Method of data collection is done by passing the question form on the overall Employee population PT Kaltrabu Indah tours & Travel Banjarmasin totalling 35 people who then established as the sample of respondents with saturated samples or samples (total as many as 35 people) census respondents. Using quantitative and qualitative analysis also linear regression program simple and multiple linear regression as well as using software MS Excell and SPSS Version 20.0.The results were obtained as follows: Partially work culture influence the Employee Performance PT. Kaltrabu Indah Tour & Travel Banjarmasin significant effect. And Partially Organizational Citizenship Behavior influence the Employee Performance PT. Kaltrabu Indah Tour & Travel Banjarmasin significant effect. Simultaneously influence Work Culture and Organizational Citizenship Behavior Employee Performance PT. Kaltrabu Indah Tour & Travel Banjarmasin significant effect.